An ICT Strategy Based upon E-Teaching and E-Learning in Response to the COVID-19 Crisis in Africa - Paul L. Woomer; Welissa M. Mulei; Samuel K. Maina (Journal of International Agricultural and Extension Education, 2021)
The COVID-19 pandemic is a crisis that has gripped the world, causing governments and development agencies to search for critical measures to protect theirpeople. The situation not only represents a significant health risk buthas resulted in school closures that have disrupted agricultural education. This impedesthe attainment of Africa’s larger food security and rural transformation agendas. Six months before the advent of the pandemic, the International Institute of Tropical Agriculture initiated a pilot project, Start Them Early Program (STEP) whose goal is to reinforcepathways to careers in agriculture within secondary schools in DR Congo, Kenya,and Nigeria. The project has now been forced to rethink its approachwhile embracing information and communication technologies due to the school closures.This paper describes the process involved in thatoperational pivot, particularly concerning the shift from electronic teaching by instructors towardsdistance electronic learning by students.Key issues addressed are the consolidation of digital applications, development ofa mobile-based toolbox for use by young farmers,and constraints to device ownership. The means of addressing these concerns through working with instructors and their larger school systems are explained. Action points and resources that are recommended include the distribution of upgraded instructor workstations, a listing of relevant software applications, and the design of a mobile-based all-in-one toolkit for agriculture students and young farmers. The latter two developments have wider application in the reform of agricultural extension amongst the tech-savvy youth taking up agribusiness
Keywords: agricultural transformation; COVID-19 response; digital agriculture; distance education; STEP program